Training of personnel as a mechanism for shaping the modern organizational culture of logistics enterprises - Polynyak, Volodymyr (Herald of Economics, 2024)
Introduction. Modern logistics enterprises operate in conditions of high competition and dynamic changes in both internal and external logistics markets. This necessitates the formation of an organizational culture oriented towards responding to innovations, partner experience, the needs of logistics service consumers, processes occurring in national and global economic environments, increasing competition in the logistics services market, and the ability to orient staff towards achieving high economic efficiency in their functioning and organizational competitiveness. Among the mechanisms for achieving these tasks, the training of personnel occupies a special place. Purpose. Development of theoretical and methodological provisions regarding the substantive characteristics and construction of a personnel training system as a mechanism for shaping the organizational culture of logistics enterprises and generating proposals for their application tailored to the specifics of each type of these enterprises. Methods. The research is based on systematic and comparative approaches. The following research methods were employed: observation, analysis, and synthesis of information on the functioning of enterprises in the logistics market; expert assessment of the internal and external environments of logistics organizations; empirical diagnosis of existing professional training programs for personnel in logistics companies in Ukraine; abstraction and concretization to develop proposals for defining indicators for evaluating the results of implementing professional training programs. Results. Based on the analysis of theoretical research by domestic and foreign scholars regarding the problem of building organizational culture in enterprises and examining the mechanisms utilized therein, the hypothesis is put forth that the fulfillment of this task largely depends on the current personnel training system, which, influenced by a variety of factors, needs to be modernized and adequately aligned with the organization’s development strategy and the specifics of its activities in the logistics services market. Emphasis is placed on the multi-level nature of training and particular attention is given to the peculiarities of on-the- job training within companies. Methodological approaches to selecting training strategies in various models proposed by foreign researchers on the issue are synthesized. An assessment is made of internal and external factors affecting the effectiveness of personnel training in logistics enterprises, complemented by a characterization of the influence of factors expressing the nature of changes in their functional activities amidst contemporary challenges in domestic and international logistics services markets. A comparative analysis of the specificity of providing logistics services by different types of logistics enterprises and its impact on the selection of training technologies is conducted. Based on empirical research methods, an evaluation of training outcomes is conducted across three types of logistics enterprises, allowing for the identification of opportunities (and problems) in integrating cutting-edge logistics technologies into the educational process and defining a list of competencies and program outcomes that would effectively support the achievement of organizational goals and the formation of a highly efficient corporate culture. Discussions. A promising area for further scientific research could be the implementation of e-learning formats in the practice of professional development for personnel in logistics enterprises, as well as the specifics of transforming their organizational culture in the context of digitization and remote work.